A STUDY ABOUT THERMAL SIMULATION IN SOLIDWORKS IN THE CASE OF DIFFERENT GEOMETRY OF THE PROCESSED PIECES BY CUTTING - IONEL OLARU (Journal of Engineering Studies and Research, 2019)
In practice, different cutting processes are encountered, each process having different characteristics. Due to the existing friction forces between the workpiece and the cutting tool, a significant amount of heat is generated. This amount of heat can be determined by experimental measurements. This paper aims to study the way in which the temperature is propagated in the workpiece, so that the phenomenon can be understood and determined how this excessive heat can be removed from the cutting area.